GAMBARAN UJI CUKIT (SKIN PRICK TEST) ALERGEN INGESTAN PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU ANGKATAN 2014 YANG MENDERITA /MENUNJUKKAN GEJALA RINITIS ALERGI - Diantaroli, Taufan; ", Harianto; Burhanuddin, Laode (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTAllergic rhinitis is the inflammation inside the nose that is exposured by sensitized allergens. The inflammation is identified by the hypersensitive reactions such as rhinorrhea, congestive nose, itchy nose, sneezing recurrently and watery eyes excessively. The skin prick test is one of the ways that applies to discover the sentizied allergens. Ingested allergens are able to cause the recurrence of allergic rhinitis. This research was a descriptive cross-sectional research. The data was collected by using total sampling method in order to determine the description of skin prick test of ingested allergens among the 2014’s students who suffer or show the symptoms of allergic rhinitis in Riau University Medical Faculty. Around 166 respondents participated to support this research. Due to the result of the research, it figured out that around 29,52 % of the 2014’s students in Riau University Medical Faculty suffered or showed the symptoms of allergic rhinitis, the most sensitized allergens was chicken allergen (30,61%) and the least was coffee (16,33%). For the signs of allergic rhinitis on the respondent suffered or showed the allergic rhinitis’s symptoms was in food allergy, the most was concha udema ( 90%) and adenoid facies are not found on respondents.Keyterms : Skin Prick Test, Ingested Allergens, Allergic Rhinitis